A study about the organizational stress in the software industry - Kiran Kumar Thoti; Roselina Ahmad Saufi (2013)
The paper briefing about the 'Occupational Stress'and reason for the stress in the organization and causes of the stress, Today world is working fast and production and turnover is the main agenda for the market. Due to the more burdens, employees are facing lot of problems in the market and problems affect their family life also. Stress is nothing about work load and it is the form of energy to make the person to work honestly with their rules. The study found that both occupational stress and negative life events are related to negative outcomes, although the impact made by occupational stress is greater. 'Occupational Stress'is stress involving work. Stress is defined in terms of its physical and physiological effects on a person, and can be a mental, physical or emotional strain. It can also be a tension or a situation or factor that can cause stress. Occupational stress occurs when there is a discrepancy between the demands of the environment / workplace and an individual's ability to carry out and complete these demands. Often a stressor can lead the body to have a physiological reaction which can strain a person physically as well as mentally. One of the main causes of occupational stress is work overload.